Spectrophotometric Determination of Flutamide, Nimesulide and Meloxicam - Murthy, T.K.; Reddy, M.N.; Dharma Reddy, M.; Sankar, D.G. (Asian Journal of Chemistry, 2010)
Three simple and sensitive visible spectrophotometric methods have been developed for the assay of flutamide, nimesulide and meloxicam in bulk samples and pharmaceutical formulations. All the methods are based on the oxidation of the drug with a known excess of oxidant, potassium permanganate (KMnO4). The excess permanganate is determined using the dye, Fast Green FCF (FGFCF) at 625 nm. The results obtained are reproducible and are statistically validated.